2019
DOI: 10.1038/s41893-019-0405-0
|View full text |Cite
|
Sign up to set email alerts
|

Governance in socioeconomic pathways and its role for future adaptive capacity

Abstract: Weak governance is one of the key obstacles for sustainable development. Undoubtedly, improvement of governance comes with a broad range of co-benefits including countries' abilities to respond to pressing global challenges such as climate change. However, beyond the qualitative acknowledgement of its importance, quantifications of future pathways of governance are still lacking. This study provides projections of future governance in line with the Shared Socio-economic Pathways (SSPs). We find that under a "r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 45 publications
0
90
0
Order By: Relevance
“…Additional global extensions support analyses across a wide range of sectors, including air pollution 25 , health 26 , water 27 , forest management 28 and oceans 29 . Extensions to support analysis of violent conflict 30 and governance 31 represent progress in topics that were previously under-served by scenarios. For instance, in one study that found large direct impacts of climate change on violent conflict to be unlikely, conflict propensity varied widely between SSP1 and SSP3 (ref.…”
Section: Achievementsmentioning
confidence: 99%
“…Additional global extensions support analyses across a wide range of sectors, including air pollution 25 , health 26 , water 27 , forest management 28 and oceans 29 . Extensions to support analysis of violent conflict 30 and governance 31 represent progress in topics that were previously under-served by scenarios. For instance, in one study that found large direct impacts of climate change on violent conflict to be unlikely, conflict propensity varied widely between SSP1 and SSP3 (ref.…”
Section: Achievementsmentioning
confidence: 99%
“…GMDH is a self-organization algorithm that has been used successfully for pattern recognition, optimization of complex systems modeling, and prediction problems, and it is also called the polynomial of the Ivakhnenko equation [63,64]. This algorithm can predict the value ofŷ i from an approximate function ( ∧ f ), for each input vector (X), which is shown in Equation (1). The basic form of a relation between input and output data can be declared as a discrete type of the Volterra functional series, referred to as the Kolmogorov-Gabor polynomial.…”
Section: Group Methods Of Data Handling (Gmdh)mentioning
confidence: 99%
“…The concept of sustainable development as a new concept, process, and undeniable fact has emerged in the policies of major governments, and plays a key role in the development of human societies [1][2][3]. Sustainable development is, generally, a combination of the three social, economic, and environmental goals in which political goals are involved.…”
Section: Introductionmentioning
confidence: 99%
“…3 reflects the severity of the difference in levels of the GII, and the importance of near-term improvements for less well-off regions. As it is the case for other indicators of socio-economic development 38,40 , the rates of improvement in the GII towards gender equality are highest up to 2050 in these scenarios. Less optimistic development pathways show a linear continuation of current trends or even a slow-down.…”
Section: Resultsmentioning
confidence: 75%
“…So far, the SSPs storylines have been quantified in future trajectories of income 34,35 , population 36 , education 36 , urbanization 37 , the Human Development Index 38 , inequality 39 , and governance 40 . Gender inequality is qualitatively featured in the scenarios' storylines focusing on the demographic and human development elements (see Table 1), and is to a certain extent reflected in the measures of discrepancies in educational attainment between men and women in the population projections by age and sex 36 .…”
Section: Resultsmentioning
confidence: 99%